Early detection and monitoring of hearing loss in vestibular migraine: Extended high-frequency hearing - Guo, Zhaoqi; Wang, Jun; Liu, Dan; Tian, E.; Chen, Jingyu; Kong, Weijia; Zhang, Sulin (Frontiers in Aging Neuroscience, 2023)
Background: Vestibular migraine (VM) mainly presents recurrent vestibular symptoms and migraine, and auditory symptoms are common as well. Nevertheless, audiological features, especially hearing at extended high-frequency (EHF) are not clear. Methods: Cross-sectional study was conducted on patients with VM who satisfied the diagnostic criteria. Auditory-vestibular test and psychological assessment were performed. The predictive role of PTA at EHF for hearing loss at SF was evaluated by Logistic regression. Results: Fifteen patients with pVM and 22 patients with dVM were recruited. In total, vestibulo-visual symptoms (83.78%) and internal vertigo (54.05%) were the most two vertigo types. The vertigo attack persisted <5 min in about 57% of patients, against 5min-72h in 43% and lingered for over 72 h in 8%. About 87% of patients had psychological disorders. Most of the patients with VM (92%) suffered from hearing impairment at EHF and 68% had hearing loss at SF, substantially higher than their complaints (43%). Moreover, the cut-off value (57dB) of the mean hearing threshold at EHF worked well in predicting the hearing loss at SF (AUC, 0.827), outperforming DPOAE (AUC, 0.748). Conclusion: The clinical manifestations of VM are heterogeneous. The rate of hearing loss was considerably higher than that of actual complaints. Moreover, patients with VM tended to have bilateral hearing loss at EHF and high frequency. The cut-off value of the mean hearing threshold at EHF was effective in predicting the hearing loss, supporting its utility in the early detection of hearing loss and monitoring of the disease progression.